The effect of motivation in managing employee absenteeism : a case study of a commercial bank in South Africa - Maphosa, Thapelo Happy (My University, 2024)
The study was conducted in one of the commercial banks in South Africa. The bank has about 500 branches across the country and is known to be doing well in implementing the wellness programmes and in managing absenteeism. Therefore, the aim of the study was to investigate the effect of motivation on the management of absenteeism in that particular bank. The objectives of the study revolved around the influence of motivation on absenteeism and on the strategies used by the bank to reduce absenteeism. The study adopted interpretivism research paradigm, with the qualitative research method to collect data. Therefore, a case study research design was used to get an in-depth understanding on how absenteeism was managed. The semi-structured interviews were conducted with the purposefully selected participants from selected branches. Thirty-two employees of the bank participated in the study. The research findings found that indeed motivation plays a role in the management of absenteeism at the bank as many of the employees refrained from being absent from work due to incentives such as cash bonuses, salaries which can fluctuate depending on their performance. External motivators placed by the bank such as targets were also reported by many of the employees to be another strong reason why they barely went on leave. The study concluded that employees should be encouraged to take leave on their given days to avoid burn out. The study therefore, recommended that the commercial bank should increase the annual leave days from 22 days to 25 days to allow the employees to have enough rest and to attend to other personal matters.
Thesis (MBA.) -- University of Limpopo, 2024
Keywords: Managing employee absenteeism; Commercial banks; South Africa; Employee motivation -- South Africa; Employee health promotion; Absenteeism (Labor)